Clinico-epidemiological and sociodemographic profile of patients with hemophilia in the Brazilian Amazon: High prevalence of hepatitis C infection and its possible corrrelation with inhibitor development - Santos, Enzo Miranda; Silva, Jean de Melo; Barbosa, Anderson Nogueira; Pontes, Gemilson Soares (Frontiers in Public Health, 2022)
Hemophilia is a recessive genetic disease caused by a mutation on the X chromosome that has been linked to a high risk of transfusion-transmitted infections, especially sexually transmitted infections. The purpose of this retrospective study was to characterize the clinical and epidemiological profile of patients with hemophilia in the Northern Brazilian state of Amazonas. We assessed clinical, laboratory and sociodemographic data of hemophiliac patients (n = 311) for the period 2011 to 2019. The majority of the study population was composed of people with a low level of education aged 21-30 years old. The prevalence of HCV, HBV and HTLV-1/2 infections among the study population were 10.52%, 0,52%, and 1.05%, respectively. No HIV infection was found among the patients. Between 2011 to 2015 the prevalence of HCV increased by over 100% and the incidence peaked in 2013. The severe hemophilia was associated with the presence of inhibitor factor (Odds Ratio [OD] 9.83; 95% IC: 3.41-27.62, p<0.0001) or target joint (OD 6.59; 95% IC: 3.27-13.34, p<0.0001). The presence of inhibitor was positive and significantly correlated with HCV infection (r=1.00, p<0.0001). Our results showed that HCV infection is highly prevalent in patients with hemophilia and might be involved in the development of inhibitors. Thus, these data provide new insights into the clinical and epidemiological profile of patients suffering from hemophilia in the Northern Brazilian state of Amazonas.